2016
DOI: 10.1097/brs.0000000000001524
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy for Low Back Pain in Elderly Degenerative Lumbar Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…This treatment is based on the concept of polymethyl methacrylate (PMMA) injection in the disc space in advances stages of degeneration with vacuum phenomenon, acting as a stabilizer intervertebral spacer, this treatment has demonstrated low back and leg pain improvement and partial correction of spinal balance in unbalanced cases with low complication rates and short hospital stay. [9][10][11] Yamada et al 23 reported improvement in low back pain in 109 patients with degenerative lumbar scoliosis treated with percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI), although the name of the procedure differs, the concept is the same. A proper patient selection is necessary, with correct identification of the pain source and some image characteristics may contribute to decrease the risk of some complications such as adjacent vertebral fracture, cement leakage, or disc material protrusion associated with PMMA injection.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment is based on the concept of polymethyl methacrylate (PMMA) injection in the disc space in advances stages of degeneration with vacuum phenomenon, acting as a stabilizer intervertebral spacer, this treatment has demonstrated low back and leg pain improvement and partial correction of spinal balance in unbalanced cases with low complication rates and short hospital stay. [9][10][11] Yamada et al 23 reported improvement in low back pain in 109 patients with degenerative lumbar scoliosis treated with percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI), although the name of the procedure differs, the concept is the same. A proper patient selection is necessary, with correct identification of the pain source and some image characteristics may contribute to decrease the risk of some complications such as adjacent vertebral fracture, cement leakage, or disc material protrusion associated with PMMA injection.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (axial pain) is often the main symptom at onset and the chief complaint at the first visit to the clinic for DS. Recent studies have shown that paraspinal muscle spasm caused by sagittal and coronal imbalance is the main mechanism of low back pain [ 23 ]. Unfortunately, dramatic pain relief is not established in some patients, and 15–30% continue to experience chronic pain in the months and years after surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 ASD has been shown to dramatically negatively affect quality of life and surgery to correct these deformities can significantly improve both spinal alignment and health-related quality of life. [3][4][5][6][7] Correcting spinal deformity is demanding for both the surgeon and the patient; it is fraught with post-operative complications, including mechanical complications necessitating additional surgery that is time consuming, painful, and expensive. [8][9][10] Proximal junctional kyphosis (PJK), a change in proximal junctional sagittal Cobb angle of 10 and at least 10 greater than preoperative angle, is a devastating mechanical complication of ASD surgery that has been posited to be multi-factorial, influenced by biology, bone quality, neurological disorders, construct factors, and alignment.…”
Section: Introductionmentioning
confidence: 99%